Effects of domestic factors on outward foreign direct investment (OFDI) in developing countries – a preliminary study of Malaysia / Rosfadzimi Mat Saad and Abd Halim Mohd Noor - Mat Saad, Rosfadzimi; Mohd Noor, Abd Halim (Division of Research, Industrial Linkages and Alumni, UiTM Cawangan Melaka, 2011)
Foreign direct investment, FDI in the area of globalization, is no longer limited to the developed nations. Increasingly FDIs between developing countries are rivalling traditional FDIs. Outward Foreign Direct Investment, OFDI is one of the measures to indicate the performance and capability of developing countries enterprises. Malaysia as a developing economy is undertaking OFDI due to the limitation of local resources and to search for new markets. Multinational corporations, MNCs seek from other countries mainly for cheap labour, law resource prices, and new market for their products and services. This paper studies the determinants of OFDI by Malaysian based MNCs. It focuses on the trends, patterns and domestic factors that push off Malaysian firms to be involved in OFDI. It will also be looking at domestic drivers such as market size, cost of skilled labour and the availability of natural resources in determining the factors influencing Malaysian OFDI. The period under study is from 1980 to 2009. Simple multiple regression analysis is used in the study. Among the variables used to proxy domestic factors; cost of skilled labour and natural resources availability are found significant in influencing OFDI.